RESPONSES AGAINST POLICE MEMBERS WHO COMMIT NARCOTICS ABUSE (Study at Padangsidimpuan Police) - Dalimunthe, Abdul Rahman; Simatupang, Nursariani (Inspiring Law Journal, 2024)
Indonesia is on the highest list of countries targeted for the distribution of illegal narcotic drugs. In several cases there are police officers who abuse their authority as law enforcement officers and are involved in the abuse of narcotics and psychotropic substances, especially storing evidence for buying and selling and using it. The purpose of this research is to find out the modus operandi of police officers who abuse narcotics, to find out the factors that cause narcotics abuse by police officers, and to find out efforts to deal with police officers who abuse narcotics. This research is empirical juridical research. The research data sources are data originating from Islamic Law, primary data and secondary data. Data collection tools in this research are interviews and documentation studies. Based on the research results, it can be understood that the modus operandi of police officers who abuse narcotics is to embezzle evidence by keeping the narcotics found and reselling them. Apart from that, there are also those for personal use. Factors that cause narcotics abuse by police officers are environmental factors, economic factors, family factors, psychological and mental factors, weak faith factors, and weak supervision from leaders/superiors. Apart from that, it is also for fun and increasing stamina. Efforts to deal with police officers who abuse narcotics include preemptive efforts by providing education about the dangers and impacts of narcotics abuse, preventive efforts by carrying out urine tests, spiritual and mental development, and close supervision. And repressive efforts by conducting assessments or rehabilitation of police officers involved in narcotics abuse and providing disciplinary guidance so that they do not repeat their actions again by making an integrity pact